PENANGANAN KASUS TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI BAWAH UMUR DI WILAYAH HUKUM WONOGIRI - Alvian Muhammad Agil; Hanuring ayu; Nourma Dewi (Sebelas Maret University, 2026)
Sexual violence against minors is one of the most serious and complex crimes in the Indonesian criminal justice system. The issue of sexual violence against minors is not only a legal issue but also a complex and multidimensional social problem. A more comprehensive approach is needed, integrating legal, social, and psychological aspects. This research is an empirical legal study. The legal process for child sexual violence cases in Wonogiri is carried out in an integrated manner, from investigation to court decision, prioritizing the best interests of the victim. The Women and Children Protection Unit (PPA) of the Wonogiri Police plays an active role in law enforcement while providing psychological protection and coordinating victim recovery through a child-friendly approach. The synergy between prosecutors and judges in implementing the Child Protection Law and the Child Protection and Child Protection Law demonstrates the police's commitment to realizing justice that is just, humane, and pro-child. Handling child sexual violence cases in Wonogiri faces complex obstacles, ranging from psychological trauma to social stigma and limited human resources. Therefore, strengthening the protection system and strengthening the capacity of law enforcement is necessary.